Traffic noise mapping using inverse distance weight interpolation technique : a case study in Bandar Kulim - Norina Omar,; Ahmad Fauzi Al-Faid Ahmed Azlee,; Mufarrahah Mayadi,; Nur Izzah Hazwani Mohd Amin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Traffic noise pollution is one of the problems in the urban environment as a result of rapid economic development which has led to an increase in the volume of diversified motor vehicle traffic flows. This condition may affect the well-being and human health as well as its surroundings if exposed to high noise levels for a long period of time or continuously. Therefore, this study was conducted to measure the level of traffic noise at 15 selected observation stations around Kulim city, Kedah. Next, the noise distribution coverage area is mapped by using Inverse Distance Weight (IDW) interpolation technique. Sound data was measured in the morning, noon, evening and night of working and non-working days by using the Sound Level Meter device. Sound observation data was analyzed to depict the concentration areas of traffic noise at the station involved in form of map visualization. Noise level comparisons were analyzed together with Department of Environment (DOE) and World Health Organization (WHO) standards. The results of the study found that all the sampling stations exceeded the standard limits allowed on working days as well as non -working days for urban and commercial land-use types. The mean values of the highest noise levels (Leq) on working days and non-working days at day times were 78.2 (S7) and 80.3 dBA (S5) respectively. Meanwhile, the highest noise level readings recorded on working days and not working at night were 76.6 and 76.9 dBA respectively, which involves observation stations 2 and 3. Several mitigation strategies were stated to overcome the problem of traffic noise in the city as a measure to curb noise pollution in the affected areas.